Application of an Inclined Settler for Cell Culture-Based Influenza A Virus Production in Perfusion Mode - Coronel, Juliana; Gränicher, Gwendal; Sandig, Volker; Noll, Thomas; Genzel, Yvonne; Reichl, Udo (Frontiers in Bioengineering and Biotechnology, 2020)
Influenza viruses have been successfully propagated using a variety of animal cell lines in batch, fed-batch, and perfusion culture. For suspension cells, most studies reported on membrane-based cell retention devices typically leading to an accumulation of viruses in the bioreactor in perfusion mode. Aiming at continuous virus harvesting for improved productivities, an inclined settler was evaluated for influenza A virus production using the avian suspension cell line AGE1.CR.pIX. Inclined settlers present many advantages as they are scalable, robust, and comply with cGMP regulations, e.g. for recombinant protein manufacturing. Perfusion rates up to 3000 L/day have been reported. In our study, successful growth of AGE1.CR.pIX cells up to 50 x 106 cells/mL and a cell retention efficiency exceeding 96% were obtained with the settler cooled to room temperature. No virus retention was observed. A total of 5.4–6.5 x 1013 virions were produced while a control experiment with an ATF system equaled to 1.9 x 1013 virions. For infection at 25 x 106 cells/mL, cell-specific virus yields up to 3474 virions/cell were obtained, about 5-fold higher than for an ATF based cultivation performed as a control (723 virions/cell). Trypsin activity was shown to have a large impact on cell growth dynamics after infection following the cell retention device, especially at a cell concentration of 50 x 106 cells/mL. Further control experiments performed with an acoustic settler showed that virus production was improved with a heat exchanger of the inclined settler operated at 27°C. In summary, cell culture-based production of viruses in perfusion mode with an inclined settler and continuous harvesting can drastically increase influenza A virus yields and possibly the yield of other viruses. To our knowledge, this is the first report to show the potential of this device for viral vaccine production.